Transition to Agroecological Practices: Positive Effects on Streams and Biofilms - Mujica, Micaela; De Geronimo, Eduardo; Nicolosi Gelis, María Mercedes; Pecile, María Agostina; Paredes del Puerto, Juan Martín; Mosca, Agustín Ignacio; Fanelli, Silvia; Jensen, Roberto; Cordero, Tómas; Paracampo, Ariel; Cochero, Joaquín (Wiley, 2025)
Transformations in agricultural practices, particularly regarding chemical inputs such as pesticides, affect physical and chemical characteristics and biotic communities of streams. Currently, many conventional production systems are transitioning to economically and environmentally more sustainable production, which aims to reduce the use of synthetic inputs. However, it remains unclear whether agroecological practices positively impact the environment. Here, we compared physical and chemical characteristics and the toxicity of sediments from streams in areas of conventional and agroecological transition horticultural practices as well as reference areas. Additionally, the effects of horticultural practices on stream biofilms were assessed in 7-day bioassays, measuring chlorophyll-a, extracellular polymeric substance concentrations, ash-free dry weight, and diatom motility. In areas with conventional horticulture, pesticides were more frequent and had higher concentrations than in areas with agroecological horticulture. This was reflected in biofilms, with lower algal biomass and higher diatom cell motility under conventional horticulture. Our study suggested that the transition to agroecological practices, even in the early stages, had positive effects on aquatic ecosystems, and we found similarities in pesticide use and biological characteristics between sites with agroecological horticulture and less-impact sites, for example, grasslands sites. This study reports and integrates the effects of a complex mixture of contaminants used in intensive horticulture, providing a more realistic assessment of their environmental consequences.